Pertambahan Alami (Natural Increase) Sapi Potong Di Kecamatan Waelata Kabupaten Buru - Papilaya, Bercomien J.; Rajab, Rajab; Holak, Achmad F R (Jurnal Agrosilvopasture-Tech, 2024)
This research is useful to determine the natural increase in Kecamatan Waelata, Buru Regency. The research was conducted in Kecamatan Waelata, Buru Regency. The selection of sample villages and determination of respondents used purposive sampling. Total respondents were 30 farmers. Data collection was conducted through interviews by applying questionnaires and field observations. Data analysis was conducted using descriptive statistics by calculating the percentage of births and mortality, sex ratio, birth and mortality ratio, birth index, mortality in certain age categories, and natural increase. The results showed that in Kacamatan Waelata, Buru regency was dominated by adult females which amounted to 44.93%, the percentage of births to female parents was 63.44% and to the population 28.50%, the percentage of mortality was 8.21%, and the value of natural increase in Waelata regency was very low at 20.29% to the population. Keywords : Cattle, births, mortality, natural increase Penelitian ini berguna agar mengetahui pertambahan alami pada Kecamatan Waelata Kabupaten Buru. Penelitian diselenggarakan di Kecamatan Waelata Kabupaten Buru. Pemilihan desa sampel dan penentuan responden memakai purposive sampling. Total responden sebanyak 30 peternak. Pengumpulan data diselenggarakan lewat wawancara melalui menerapkan kuesioner serta observasi dilapangan. Analisis data diselenggarakan secara statistik deskriptif melalui menghitung persentase kelahiran dan kematian,rasio sex, rasio kelahiran dan kematian, indeks kelahiran, kematian pada kategori umur tertentu, dan natural increase. Hasil penelitian menunjukan bahwa di Kacamatan Waelata Kabupaten Buru didominasi oleh betina dewasa yaitu sebesar 44,93%, persentase kelahiran terhadap induk betina adalah sebanyak 63,44% dan terhadap populasi 28,50%, persentase kematian sebesar 8,21%, dan nilai natural increase di kecamatan waelata kabupaten sangat rendah yaitu sebesar 20,29% terhadap populasi Kata Kunci: Ternak sapi, kelahiran, kematian, natural increase